Environmental and economic drivers of subjective well-being: evaluating the effects of pollution, income growth, and income inequality in Pakistan - Saima Mehmood; Faiza Sajjad; Agha Amad Nabi; Ishfaq Ahmad; Imran Naseem; Khalid Zaman (EQA, 2024)
Environmental pollution has emerged as an increasingly severe issue on a global scale, significantly impacting individuals' well-being due to the influence of environmental factors. Moreover, higher income levels play a crucial role in poverty reduction, enhanced productivity, improved quality of life, and overall national development. In the context of Pakistan, both polluted air and income inequality have detrimental effects on the well-being of its population. This research aims to investigate the influence of environmental pollution and income growth on subjective well-being in Pakistan, using data from the period spanning 1975 to 2022. The study employs the Autoregressive Distributed Lag (ARDL) technique to assess the short-term and long-term impacts of environmental pollution and income growth on economic well-being. The findings indicate that CO2 emissions, solid waste, and GDP per capita have a negative long-term impact on subjective well-being, while CO2 emissions and initial solid waste management have a positive short-term effect. Additionally, income inequality exerts a negative short-term influence and a positive long-term effect on subjective well-being. The Granger causality estimates confirm the bidirectional relationship between the country's income and subjective well-being. Moreover, subjective well-being Granger-causes environmental factors. Solid waste, environmental factors, and income inequality influence the country's income. The impulse response function suggests that carbon emissions, income growth, and solid waste are likely to exert a positive impact on subjective well-being, while income inequality and PM2.5 are likely to decrease subjective well-being over the next 10 years. The variance decomposition analysis suggests that PM2.5 is likely to exert the greatest variance shock on subjective well-being, followed by solid waste management and the country’s per capita income over the next 10 years. These results highlight the need for Pakistan to prioritize sustainable environmental practices to achieve a clean and healthy environment. Furthermore, the country should promote economic inclusion and strive to create decent employment opportunities, ultimately leading to higher incomes and improved well-being for its citizens.